EVALUASI SISTEM IDENTIFIKASI GENDER BERDASARKAN NIK PADA PEMBELIAN TIKET ONLINE KERETA API INDONESIA (KAI ACCESS) - Ilhan Mansyah; Mareanus Lase; Walim Walim; Dian Ardiansyah (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
This study aims to evaluate the Usability level of the gender identification system based on the National Identification Number (NIK) in the KAI Access application used for online train ticket purchases. The system was developed by PT Kereta Api Indonesia (KAI) to enhance passenger comfort and safety through seat arrangement based on gender. This study employed a quantitative approach with the System Usability Scale (SUS) method. Data were collected from 100 KAI Access users through an online questionnaire. The results showed that the average SUS score was 76.18, classified as Category C (Okay), indicating that the system has good Usability and is acceptable to users. However, some respondents suggested improvements in system notifications and user guidance.